Short-Term Outcomes of Neuromuscular Electrical Stimulation in Critically Ill Patients. Issue 2 (April 2023) - Mahran, Ghada S. K.; Mehany, Mogeda M.; Abbas, Mostafa S.; Shehata, Abd-ElRady; AbdElhafeez, Azza S.; Obiedallah, Ahmed A.; Mohamed, Sherif A.
Abstract : Muscle weakness acquired in the intensive care unit (ICU) adversely affects outcomes of ICU patients. This article reports the short-term respiratory effects of neuromuscular electrical stimulation (NMES) in critically ill patients. Patients were randomly assigned to an intervention group (NMES + conventional physiotherapy) and a control group (sham NMES + conventional physiotherapy). The application of NMES in the intervention group resulted in a significant decrease in the duration of mechanical ventilation and reduced the number of weaning trial failures. Other positive outcomes included reductions in the length of ICU stays and decreased mortality when compared with the control group.